Foot Health Assessment Among People with Diabetes for Healthcare Professionals - Khunkaew, Saneh; Supsung, Alisa; Thaiwong, Anucha (Journal of Research in Nursing-Midwifery and Health Sciences, 2019)
The prevalence of diabetic foot ulcers increases significantly every year among people especially who cannot control their blood glucose levels. High blood glucose levels can cause diabetic neuropathy and sweat gland dysfunction which can develop foot ulcers. Amputation may be considered where the combination of bacterial infection and long-term unhealed foot ulcers are becoming to gangrenous. Foot health assessment among people with diabetes is important for healthcare professionals and can prevent the development of unhealed diabetic foot ulcers. In addition, it can reduce the amputation rate among people with diabetes. The purpose of this article was to provide a foot examination process including the details of using Semmes-Weinstein monofilament (10g), Tuning fork, and the Ankle Brachial Index (ABI) measurement, classification risk of diabetic foot ulcers, and practice guidelines for preventing diabetic foot ulcers regarded as high risk. All the knowledge and clinical assessments can assist the health care providers in the assessment of people with diabetic foot ulcers and prevent severe diabetic foot ulcers in areas lacking a specialist or primary care provider able to make a referral to a specialist.